Knowledge Management and Its Relationship To Work Quality In The Iraqi Central Gymnastics Federation - Abdul Hussein Majid Muhammad; Ali Saad Aziz (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The research sought to identify knowledge management and work quality and the relationship between them in the National Sports Federation in the game of gymnastics. Utilizing correlational correlations and the survey method, the researchers employed a descriptive strategy. The research community was determined from the workers in the National Sports Federation, numbering (120) workers. The community was divided into (20) workers for the exploratory experiment and (100) workers for the preparation and application experiment. The scientific foundations of the two scales (reliability and validity ) were used through the ability to distinguish, internal consistency and half-split. The researchers concluded that the prevailing work quality in the Federation has a set of constituent elements that the Federation must realize and work to balance between them to reach a better work environment that accompanies the activity of the workers. The researchers recommended that the Federation and the sample study must know the steps and mechanisms related to knowledge management and search for methods through which they can discover the relationship and impact with the performance of the working individuals and guide decision-makers in the Federation to the path that can be taken to reach that activity that links knowledge management and work quality.